Faktor Influencing the Vacuum Freezing Rate of Liquid Food - Armansyah H. Tambunan (Jurnal Keteknikan Pertanian, 2000)
Many,freezing methods, mechanicul as well as cryogenic, have been in wide application in food industries. Each method has its own advantage, but in regard with the food quality, freezing rule can be accomplished by the method is one of the tnost important factors. Nowadays, many researchers are conducting experiment in order to enhance thefi.eezing rate. This paper deals with the advantage of vacuum freezing method in enhancing the freezing rate and its applicability for liquidfood.Experinrent was carried out for distilled water, milk, and fruit juice using multi-purpose vacuum equipment. As easily predicted, minimum pressure of the freezing chamber determine temperature of the product. Vuriation on the fruit juice concentration shows that faster freezing rate canbe achieved if the product is more dilute. The experiment also showed that freezing rute obtained by vacuumj-eeziirg was signijkantly faster than contact plate freezing method.